Active labor market policy in Germany: is there a successful policy strategy? - Fertig, Michael; Schmidt, Christoph M.; Schneider, Hilmar (Discussion paper series, 2002)
Each year Germany and many other developed economies spend tens of billions of Euros on active measures of employment promotion with the explicit aim of contributing to the reduction of unemployment. Yet, high unemployment has universally been a persistent problem throughout the last two decades, raising the question as to the actual effect of the measures of employment promotion. This paper contributes to the received literature by investigating whether a specific strategy of active labor market policy measures can contribute to a significant reduction of unemployment on the (semi-) aggregate level of the local labor offices in Germany. To this end, we analyze ALMP in Germany in a spatially augmented regression framework. Our results suggest that a policy strategy focusing on monetary incentive schemes rather than on public employment programs is more successful.
Keywords: Arbeitspapier; Graue Literatur